Viral Culture as a Court of Public Opinion: A Socio-Technical Analysis of Digital Vigilantism and Institutional Pressures - Nuriyah Hanik Fatikhah (PT. Anagata Sembagi Education, 2026)
The rise of viral culture on social media has fundamentally reshaped the formation of public opinion, creating what can be conceptualized as a “court of public opinion” in which individuals and institutions are collectively judged outside formal legal frameworks. This study aims to analyze how viral culture constructs public judgment through the interaction of algorithmic systems, emotional engagement, and participatory digital behavior. This research employs a qualitative approach using a systematic literature review (SLR) of peer-reviewed studies published between 2021 and 2026. Data were analyzed through thematic synthesis focusing on algorithmic amplification, emotional contagion, user participation, and institutional responses to viral events. The findings reveal that viral culture operates through interconnected mechanisms in which algorithmic visibility determines content exposure, emotional reactions accelerate diffusion, and participatory audiences reinforce collective moral evaluation. These processes produce significant consequences such as digital vigilantism, public shaming, cancel culture, and institutional pressure, where legal and political systems often respond reactively to viral public opinion. The study concludes that viral culture functions as a socio-technical judicial system that transforms social media into an informal court of public opinion, where visibility and emotional intensity often outweigh procedural justice. This phenomenon highlights the growing tension between digital publics and formal institutions in contemporary society.